Pattern of Presentation of Liver Function Tests Parameters in a Tertiary Institution in Delta State, Nigeria - Orugbo, Voke Peter; Ohaju-Obodo, John (Journal of Advances in Medicine and Medical Research, 2022)
Aims: Liver function tests or "LFTs" are performed to measure liver function and identify the source of liver damage while examining the health state of the liver. The current study looked into the pattern of presentation of liver function tests values in a tertiary institution in Delta State, Nigeria. Study Design: This was a cross-sectional study. Place and Duration of Study: The study was carried out at the Delta state University Teaching Hospital (DELSUTH),Oghara, Delta State, Nigeria over a 24-month period. Methodology: The study included 1436 recruited subjects who reported to the Chemical Pathology Laboratory for LFTs at the Delta State University Teaching Hospital (DELSUTH) in Oghara, Delta State, Nigeria. The participants' ages varied from infants to people in their 70s. Results: There were no significant variations in total protein (TP) across the age groups. TP levels in neonates and infants varied from 4.73 g/dl (p>0.05). TP levels in adults varied from 6.43 to 7.75 g/dl. Total bilirubin (T.BIL) levels in adults were lower in general than in babies and neonates (p0.05). There were no gender differences in the LFTs parameters among the adult individuals. TP levels in the females (6.50 g/dl) were greater (p<0.05) than in the boys (8.84 g/dl) among the day-olds. However, after 2 weeks, the girls' TP levels (4.67 g/dl) were considerably lower (p0.05). All participants' TP levels were within reference intervals. More than 80% of subjects had substantially increased ALP levels. Infants have higher levels of bilirubin than adults. Conclusion: At least 5% of the adult subjects developed hyperbilirubinemia. Gamma glutamyltransferase (GGT), Glutamate oxaloacetate transferase (GOT), and Glutamate pyruvate transferase (GPT) levels were significantly elevated in at least 50% of all subjects, regardless of age or gender. The immediate underlying reason is unknown.